Policy Considerations regarding the Integration of Lusophone West African Immigrant Populations - Lartey, Kezia; Lundy, Brandon D. (Border Crossing, 2017)
On January 23, 2012, Resolution No. 3 enacted the National Immigration Strategy for the island nation of Cabo Verde, the first of its kind in the country. As a buffer nation to Western Europe with a rapidly developing economy and good governance indicators, Cabo Verde is transitioning from a sending and transit country to a receiving nation for African mainlanders, especially from Guinea-Bissau. How effective are these immigration policies at managing these changing mobility patterns? Are immigrants successfully integrating into host communities? How might integration be handled more effectively? This policy briefing reports integration successes and failures from ethnographic research and considers the effectiveness of Cabo Verde’s National Immigration Strategy based on these findings. Cabo Verde’s immigration policy targets structural reforms such as education, healthcare, and housing, while additional socio-cultural strategies encourage coexistence among neighbours. Three years out, our study observed positive effects, while also suggesting additional reforms.